LITERASI DIGITAL DAN KEWIRAUSAHAAN: MEMPERSIAPKAN GENERASI MUDA MENGHADAPI TANTANGAN BISNIS DIGITAL - Felix, Antonius; Sutrisno, Julius; Bernanda, Devi Yurisca; Makarawung, Reynard J.N.; Kembau, Agung Stefanus; Hong, Kristy (Jurnal Pengabdian dan Kewirausahaan, 2025)
The integration of digital literacy in secondary education is vital for fostering students' entrepreneurial skills. The Community Service Program (PKM) "Dream Business" at SMK Permata Indah and SMAK Diakonia aimed to enhance digital literacy and entrepreneurship among students and teachers, with a focus on digital marketing. Using a mixed-method approach (quantitative and qualitative), the program evaluated the effectiveness of the training. Results showed an improvement in participants' understanding, with average positive ratings for educational aspects (3.5) and objectives (3.4), though transparency needed improvement (3.2). The program emphasized TikTok as a marketing tool but also highlighted the need for a broader understanding of digital transformation and data analysis. While participants were introduced to digital tools for marketing, the primary focus remained on leveraging social media, particularly TikTok, for product promotion. This approach differed slightly from literature that stresses the importance of critical evaluation of digital content and the creation of educational, not just commercial, content. The activity prioritized practical social media marketing over broader digital business transformation, leaving gaps in critical content evaluation and advanced data analysis skills. Moving forward, similar programs should deepen material on critical content evaluation, digital analysis tools, and the integration of technology in overall business management. This will ensure participants gain not only digital marketing skills but also a comprehensive understanding of how technology can transform all aspects of business. Such an approach will better prepare the younger generation to face innovative and sustainable digital business challenges.